Determinasi Nilai Perusahaan ( Studi Kasus Perusahaan Transportasi & Logistik Periode 2018 – 2021) - Vungky Nilamsari; Ismunawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Study aims to determine the effect of variables from firm size, leverage, total asset turnover, and digitalisasi affecting on Company Value in Transportation and Logistics sector companies that listed on the Indonesia Stock Exchange for the 2018 to 2021 period. The population in this study includes 44 Transportation and Logistics sector companies listed on the Indonesia Stock Exchange for the 2018 to 2021 period. The sampling technique used purposive sampling method and obtained a sample of 11 selected companies. This study uses secondary data in the form of financial statements that have met the criteria, and data obtained comes from financial statements that can be accessed via the website www.idx.co.id. The analysis tool used is the analysis tool multiple linear regression analysis tested using Statistical Package for the Social Science (SPSS) version 21.0. The results show that has been done leverage and total asset turnover have a significant effect on firm value , while firm size and digitalisasi have a but not significant effect on firm value.